Paul Claudel - Daniel, Yvan; Alexandre-Berues, Pascale; Autran, Michael (Paris: Auteurs, 2005)
Este texto contiene: Amériques, en chine et au Japon,Claudel,une passion pour L`Europe
Keywords: Literatura Universal